Uncovertebral joints – their structure, development and relationships with intervertebral discs of cervical spine - Porzych, Piotr; Ratuszek-Sadowska, Dorota; Pyskir, Małgorzata; Płusa, Rafał; Ogurkowski, Karol; Dzierżanowski, Maciej; Hagner, Wojciech (Journal of Education, Health and Sport, 2017)
Uncovertebral joints, also referred to as Luschka’s joints, are found from the level of second cervical vertebra down to first or second thoracic vertebra. In adults, they appear as regular spaces in annulus fibrosus between the uncinate processes and round edges of vertebral body above. Their development remains in close relationship with changes occurring in intervertebral discs. The joint space, which is formed by the fissure into the fibrocartilaginous core of the intervertebral disc, widens medially at its rear aspect for a various distance. In aged spines, this space extends into additional, smaller lateral fissures, vast and irregular in shape. It is believed that the changes in the uncinate process’ structure are the outcome of progressing dehydration and narrowing of the intervertebral discs of cervical spine. This results in remodeling of the process, which begins to expand and flatten with age. According to many authors, uncovertebral joints are small synovial articulations, that aren’t yet noticeable at age of 6 to 9 and become fully developed before the age of 18. There is some controversy on whether they should be classified as true synovial joints. Some researchers claim that they’re an outcome of degenerative processes occurring within the intervertebral discs and therefore shouldn’t be treated as a product of natural development. The presence of synovial tissue within the joints has been a point of some discussions. Recent studies conclusively shown the presence of synoviocytes in the lateral joint capsule tissue of elderly uncovertebral articulations. The purpose of this paper is to describe the structure, development and relationships of uncovertebral joints with intervertebral discs of cervical spine.